Difficulties Faced in English Language Instruction within Multilingual Educational Settings - Maradona, Andi (Edelweiss : Journal Of Innovation In Educational Research, 2023)
An individual who is able to speak, write, or comprehend more than one language is said to be multilingual from the perspective of the notion. It encompasses the utilization of two or more languages in a large number of different settings and for a wide range of different purposes. The purpose of this research is to investigate the difficulties that arise while teaching English in classrooms that have students who speak more than one language. Through the use of a study of the relevant literature, this paper investigates the various perspectives that scholars have on the subject at hand. Within the scope of this study article, the implementation of multilingual education in a number of different countries is investigated. The difficulties that are encountered by individuals who are interested in implementing multilingual education are also explored. English teachers face a big problem when they are tasked with teaching English in a multilingual setting because of the language diversity that exists within classroom areas. Due to their reluctance to make mistakes, pupils who speak more than one language frequently lack confidence when it comes to utilizing English. There is a possibility that the curriculum is not appropriate for improving students' English language skills. According to the findings of the study, a strategy that is centered on the student and takes into account the unique requirements and experiences of each learner is what is required for effective language instruction in classrooms that contain several languages